1975
DOI: 10.1055/s-0028-1098577
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study for the Prevention of Pancreatitis Following Endoscopic Retrograde Cholangio-Pancreatography (ERCP)

Abstract: Carefully measured contrast medium instillation and generalized antibiotic prophylaxis lowered the post-ERCP pancreatitis rate from earlier values of 7.38°/o to present values of 1.3°/o. Additional administration of aprotinin and glucagon has no further prophylactic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…As has been our experience with calcitonin, Cotton (3) reported that in a controlled study in 40 patients the prophylactic administration of Trasylol prior to ERCP did not influence the elevation of serum amylase, and 2 patients on Trasylol developed pancreatitis. Similarly Koch et al (5) found no benefit from Trasylol or glucagon, while Silvis and Vennes (11) found that glucagon signifi cantly reduced blood amylase levels compared to controls 24 h after ERCP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As has been our experience with calcitonin, Cotton (3) reported that in a controlled study in 40 patients the prophylactic administration of Trasylol prior to ERCP did not influence the elevation of serum amylase, and 2 patients on Trasylol developed pancreatitis. Similarly Koch et al (5) found no benefit from Trasylol or glucagon, while Silvis and Vennes (11) found that glucagon signifi cantly reduced blood amylase levels compared to controls 24 h after ERCP.…”
Section: Discussionmentioning
confidence: 96%
“…The hyperamylasemia after ERCP reaches its peak levels in a few hours and returns to normal in 1 -4 days (3,5). Nehel and Forms (6) found that hyper amylasemia occurred in 52% of their patients undergoing ERCP, with a mean peak increase in serum amylase of 185% at 4 -8 h. The results of the 1974 survey of the American Society for Gastrointestinal Endoscopy indicated that ERCP is a safe procedure in experienced hands (7).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic enzyme rise is very com mon after ERCP or endoscopic sphincterotomy (ES), currently without clinical significance although it repre sents a mild form of pancreatitis [1], As a rule, amylase and lipase elevations are transient, appear immediately after examination and seem to be directly related to a local effect of the contrast agent, to the pressure of the injection and to the number of attempts. The peak of plasma enzyme elevations is usually observed 4 h after the procedure [1], Some substances such as glucagon and aprotinin have failed to prevent transient hyperamylasemia and pancreatitis following ERCP, but an intrave nous infusion of somatostatin for 4 h is able to decrease the magnitude of the pancreatic reaction, as shown by the lower degree of hyperamylasemia and hyperlipasemia after the procedure [2,3], Also, an intravenous bolus injection of somatostatin (4 pg/kg body weight) dramatically reduces the volume of pancreatic secretion with a concomitant increase of lipase and amylase con tents.…”
Section: Introductionmentioning
confidence: 99%
“…such as acute cholangitis. An tibiotics may also decrease the prevalence of post-ERCP pancreatitis [3,14], but they do not totally prevent this complication. In this study ceftazidime prophylaxis was given to every patient.…”
Section: Discussionmentioning
confidence: 99%